The Increasing Students' Interest in Learning in Economics Subjects Through the Problem Based Learning (PBL) Method in Class XI of SMAN 2 Pasir Limau Kapas 2023 - 2024 - Bahtiar; Harahap, Fitriani (Berpusi Publishing, 2024)
This research aims to describe the increase in students' interest in learning economics subjects through the Problem Based Learning (PBL) method in class XI of SMAN 2 PASIR LIMAU KAPAS . This research was carried out in 2 cycles. In Cycle 1 and Cycle 2 this research was carried out on 8 December 202 3 - 25 January 202 4 , at SMAN 2 PASIR LIMAU KAPAS with the research subjects being class XI students in Economics for the academic year 202 3 - 202 4 totaling 36 people. In the first cycle, the percentage of students' learning completeness from Pre-cycle was 54.75, in the first cycle it increased to 79.25 and in the second cycle it became 88.25. The number of students who completed their studies also increased from pre-cycle, there were only 3 students, in cycle I there were already 25 students and in cycle II it increased again to 36 students, although not all students had completed their studies. Mastery of the material can be said to have increased because in the first to third lessons there was an increase from the first cycle of only 7.5 % , in the second cycle it increased to 62.5%. After students were given additional work by doing exercises and teacher guidance in cycle II, it increased to 62. % and after the second lesson, students were given additional assignments at home. Students who were able to master the learning material increased to 87.5%. Based on the increase in the percentage calculation, it can be concluded that learning using the Problem Based Learning (PBL) method can increase students' interest in Economics subjects in APBN and APBD material. This is proven by the increase in each cycle.